Investigation of the e?ects of lactic acid bacteria isolated from Mihalic cheese on the degradation of some pesticides from di?erent groups - İstanbullu, Yıldıray; Yılmaz, Mete; Ayanoğlu, Ergün; Demir, Sema; Çetin, Vesile; Tosunoğlu, Hakan (GIDA VE YEM KONTROL MERKEZ ARAŞTIRMA ENSTİTÜSÜ MÜDÜRLÜĞÜ, 2022)
Abstract Objective: This study was carried out to determine the e?ects of lactic acid bacteria isolated from Mihaliç cheese on the biodegradation of some pesticides from di?erent groups. Materials and methods: In the study, the e?ect of strains of Lactobacillus fermentum, Lactobacillus paracasei, Lactobacillus rhamnosus, Lactobacillus delbrueckii subsp. bulgaricus and Lactococcus lactis isolated from Mihaliç cheese preserved in Dairy Gene Bank on the degradation of some pesticides (malathion, endosulfan sulphate, alpha-endosulfan, beta-endosulfan, cypermethrin and imidacloprid) were determined by the pesticide residue analysis based on the QuEChERS method at 0, 24 and 48 hours using GC-MS/MS and LC-MS/MS systems. At the beginning of the study, pesticides were spiked at the level of 10 mg/kg (ppm). Results and conclusion: Lb. fermentum, Lb. paracasei, Lb. rhamnosus, Lb. delbrueckii subsp. bulgaricus and Lc. lactis strains signi?cantly increased the degradation rate in all pesticides compared to the control group, and time had a positive e?ect on this destruction. At the end of 48 hours, the pesticide active ingredient most destroyed was cypermethrin and the strain that destroyed the most cypermethrin was Lb. fermentum. This value decreased by 92.5% from the initial value of 10.10 ppm to 0.75 ppm. Among the strains, Lb. fermentum is the one that causes the most destruction in pesticides after 48 hours.

Özet Amaç: Bu çalışma Mihaliç peynirinden izole edilen laktik asit bakterilerinin farklı gruplarda yer alan bazı pestisitlerin biyolojik yıkımı üzerine olan etkilerinin belirlenmesi amacıyla yürütülmüştür. Materyal ve yöntem: Çalışmada Mihaliç peynirinden izole edilmiş olan, Bursa Gıda ve Yem Kontrol Merkez Araştırma Enstitüsü Müdürlüğü, Süt Ürünleri Gen Bankası bünyesinde muhafaza edilen Lactobacillus fermentum, Lactobacillus paracasei, Lactobacillus rhamnosus, Lactobacillus delbrueckii subsp. bulgaricus ve Lactococcus lactis suşlarının bazı pestisitlerin (malathion, endosulfan sulfat, alfa-endosulfan, beta-endosulfan, cypermethrin ve imidacloprid) yıkımına olan etkileri; QuEChERS metodu temelli pestisit kalıntısı analizi ile GC-MS/MS ve LC-MS/MS sistemleri kullanılarak 0., 24. ve 48. saatlerde belirlenmiştir. Çalışmanın başında 10 mg/kg (ppm) seviyesinde pestisit ilavesi yapılmıştır. Tartışma ve sonuç: Lb. fermentum, Lb. paracasei, Lb. rhamnosus, Lb. delbrueckii subsp. bulgaricus ve Lc.lactis suşlarının tüm pestisitlerde yıkım oranını kontrol grubuna kıyasla anlamlı ölçüde arttırdığı ve zamanın bu yıkıma olumlu etkide bulunduğu tespit edilmiştir. 48 saat sonunda en fazla yıkıma uğrayan pestisit etken maddesi cypermethrin olurken cypermethrin etken maddesinde en fazla yıkım yapan suş Lb. fermentum olmuştur. Bu değer başlangıçtaki 10,10 ppm değerinden %92,5 oranında azalma ile 0,75 ppm'e düşmüştür. Suşlar içerisinde de 48 saat sonunda pestisitlerde en fazla yıkım yapanın Lb. fermentum olduğu saptanmıştır.
Mihaliç peynirinden izole edilen laktik asit bakterilerinin farklı gruplarda yer alan bazı pestisitlerin yıkımı üzerine etkilerinin incelenmesi